2019
DOI: 10.3892/mco.2019.1837
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic impact of serum transthyretin in patients with non‑small cell lung cancer

Abstract: The identification of novel biomarkers is of great importance for improving the outcome of patients with non-small cell lung cancer (NSCLC). Therefore, the aim of the present study was to determine whether the serum transthyretin (TTR) level could be used as a novel prognostic biomarker for patients with NSCLC. Serum TTR levels, and nutritional and inflammatory parameters were examined prior to treatment in 42 patients with NSCLC. Candidates for independent predictors of prognostic factors were subjected to un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 23 publications
(21 reference statements)
2
2
0
Order By: Relevance
“…2A ). With this dataset, we could confirm several markers on a protein level that had previously been shown on RNA level 23 , such as mucin-5B (MUC5B), a glycoprotein that is secreted in the lung and is associated with poor prognosis in ADC 24 , kininogen 1 (KNG1), and serum transthyretin (TTR), which has been shown to be associated with poor outcome 25 . In SCC we could confirm apolipoprotein 1 (APOA1) which has previously been described as inversely correlated with the risk of lung cancer 26 .…”
Section: Resultssupporting
confidence: 53%
“…2A ). With this dataset, we could confirm several markers on a protein level that had previously been shown on RNA level 23 , such as mucin-5B (MUC5B), a glycoprotein that is secreted in the lung and is associated with poor prognosis in ADC 24 , kininogen 1 (KNG1), and serum transthyretin (TTR), which has been shown to be associated with poor outcome 25 . In SCC we could confirm apolipoprotein 1 (APOA1) which has previously been described as inversely correlated with the risk of lung cancer 26 .…”
Section: Resultssupporting
confidence: 53%
“…Kaplan Meier analysis further showed that OS and DFS in patients with high TTR were signi cantly longer than those in patients with low TTR. This is consistent with the previous results that the abnormal expression of TTR is associated with poor clinical prognosis in lung cancer and gastrointestinal cancers [19,20]. Meanwhile, subgroup analysis showed that in patients with stage I and II lung cancer, OS and DFS of patients with high TTR were signi cantly longer than those with low TTR, indicating that TTR also has a value prognosis for early lung cancer.…”
Section: Discussionsupporting
confidence: 92%
“…Several publications reported a role for prealbumin in predicting prognosis (mostly survival) in various clinical conditions such as gastric cancer [37], lung cancer [38] and cardiovascular diseases [39].…”
Section: Serum Visceral Proteins As Biomarkers Of the Nutritional mentioning
confidence: 99%